Biological safety of Electroacupuncture with STS316 needles - Kwang-Ho Choi; Sun Hee Yeon; Seong Jin Cho; O Sang Kwon; Sanghun Lee; Su Yeon Seo; Suk-Yun Kang; Yeonhee Ryu (BMC, 2019)
Abstract Background Electroacupuncture (EA) is often used in clinical settings due to its analgesic effect, but its safety has not been verified due to the lack of clear criteria. This study examined the critical range of the corrosion of stainless steel types STS304 and STS316, which have been used clinically, and the relationship between needle corrosion and cell necrosis. Method The critical point of corrosion for STS304 and STS316 was identified by varying the time, frequency, and stimulation intensity. In a tissue necrosis experiment, EA stimulation was applied to rats using STS316 needles with different thicknesses at maximum intensity for 60 min, and the presence of corrosion and tissue necrosis was determined. A cytotoxicity experiment was also conducted and assessed the needles and tissue necrosis. Results The results showed that STS316 was more stable than STS304 and that only coated needles corroded. Furthermore, tissue necrosis was observed regardless of corrosion, and slight cell necrosis was associated with needles with corrosion. Conclusions This study demonstrated that non-coated STS316 was the most stable for EA stimulation and that corrosion byproducts and cell necrosis were not directly related.